Simplify. Assume that all variables result in nonzero denominators. Enter the expression in simplest form. The numerator and denominator must be in explanded form.

Simplify. Assume that all variables result in nonzero denominators.
Enter the expression in simplest form. The numerator and denominator must be in explanded form (i.e. not a product of factors).
$$\displaystyle\Rightarrow{\frac{{{6}{q}}}{{{q}+{1}}}}-{\frac{{{q}-{4}}}{{{q}}}}+{\frac{{{6}}}{{{q}+{1}}}}=$$

• Questions are typically answered in as fast as 30 minutes

Plainmath recommends

• Get a detailed answer even on the hardest topics.
• Ask an expert for a step-by-step guidance to learn to do it yourself.

$$\displaystyle\Rightarrow{\frac{{{6}{q}}}{{{q}+{1}}}}-{\frac{{{q}-{4}}}{{{q}}}}+{\frac{{{6}}}{{{q}+{1}}}}$$
$$\displaystyle\Rightarrow{\frac{{{6}{q}^{{{2}}}-{\left({q}-{4}\right)}{\left({q}+{1}\right)}+{6}{q}}}{{{q}{\left({q}+{1}\right)}}}}$$
$$\displaystyle\Rightarrow{\frac{{{6}{q}^{{{2}}}-{\left({q}^{{{2}}}+{q}-{4}{q}-{4}\right)}+{6}{q}}}{{{q}{\left({q}+{1}\right)}}}}$$
$$\displaystyle\Rightarrow{\frac{{{6}{q}^{{{2}}}-{\left({q}^{{{2}}}-{3}{q}-{4}\right)}+{6}{q}}}{{{q}{\left({q}+{1}\right)}}}}$$
$$\displaystyle\Rightarrow{\frac{{{6}{q}^{{{2}}}-{q}^{{{2}}}+{3}{q}+{4}+{6}{q}}}{{{q}{\left({q}+{1}\right)}}}}$$
$$\displaystyle\Rightarrow{\frac{{{5}{q}^{{{2}}}+{9}{q}+{4}}}{{{q}{\left({q}+{1}\right)}}}}$$
$$\displaystyle\Rightarrow{\frac{{{5}{q}^{{{2}}}+{5}{q}+{4}{q}+{4}}}{{{q}{\left({q}+{1}\right)}}}}$$
$$\displaystyle\Rightarrow{\frac{{{5}{q}{\left({q}+{1}\right)}+{4}{\left({q}+{1}\right)}}}{{{q}{\left({q}+{1}\right)}}}}$$
$$\displaystyle\Rightarrow{\frac{{{\left({5}{q}+{4}\right)}{\left({q}+{1}\right)}}}{{{q}{\left({q}+{1}\right)}}}}$$
$$\displaystyle\Rightarrow{\frac{{{5}{q}+{4}}}{{{q}}}}$$
So, the simplified expression is:
$$\displaystyle\Rightarrow{\frac{{{5}{q}+{4}}}{{{q}}}}$$
Have a similar question?

• Questions are typically answered in as fast as 30 minutes